STRATEGI KOMUNIKASI PADA VIDEO PEMBELAJARAN BAHASA ARAB OLEH NON PENUTUR ASLI - Firdaus, Fasich; Nor Anisa Siska; Rachmad Ramadhan (Arabic Language and Education, 2025)
With the advancement of time, Arabic language learning technology is now easily accessible through various media, including YouTube, Instagram, TikTok, and others. Arabic language content creators who are non-native speakers utilize these platforms to support Arabic language learning. They cover topics ranging from Nahwu and Shorof to the four Arabic language skills. The research method used in this article is qualitative. The researcher will focus on describing the following aspects: first, analyzing the communication strategies of non-native speakers; second, analyzing the content; and third, describing the code-switching used by instructors in the videos. The results of this study are expected to provide solutions for Arabic language learning, particularly in the field of linguistics.